PENGGUNAAN LINE SEBAGAI MEDIA KOMUNIKASI ORGANISASI: (Studi Kualitatif Deskriptif Media Sosial LINE Pada BEMP Ilmu Komuniikasi UNJ Periode 2021/2022) - Putri, Amanda Kanary; Putri, K.Y.S (JIKE : Jurnal Ilmu Komunikasi Efek, 2023)
LINE is a new media that belongs to the category of social media that functions as an instant message sender and more if it is used as a medium to communicate. LINE is considered quite effective in interacting between members and has a high level because it is equipped with features that make it easier for users to use it. The problem that must be investigated is how to use the LINE application in organizational communication at BEMP ILMU KOMUNIKASI UNJ Periode 2021/2022. The purpose of this study is to find out and describe the level of effectiveness of using LINE social media as a medium for exchanging messages and interactions between members of BEMP ILMU KOMUNIKASI UNJ Periode 2021/2022. The that authors used is a descriptive qualitative method with a sampling technique is purposive sampling which is a sampling technique by adding certain criteria including being active in the organization (BEMP ILMU KOMUNIKASI UNJ Periode 2021/2022), using the LINE application as an organizational communication medium, and actively exchanging messages. in online activities in organizations. The result of this study is that LINE media communication is much more effective, open, and convenient because there is no response that allows implementing and high spontaneity like when direct communication. LINE can cut distances, time, and also achieve the satisfaction of communication in organization.